Contrast‐induced early repolarization pattern and ventricular fibrillation. Issue 8 (15th August 2021) - Kariki, Ourania; Kontonika, Marianna; Miliopoulos, Dimitrios; Bazoukis, George; Vlachos, Konstantinos; Dragasis, Stylianos; Gouziouta, Aggeliki; Letsas, Konstantinos P.; Efremidis, Michael; Voudris, Vassilis
Abstract: Malignant arrhythmias during coronary angiography consist a complication of the procedure. Clinicians should be aware that intracoronary infusion of contrast medium can lead to physiological changes that lower the ventricular fibrillation threshold. Abstract : Malignant arrhythmias during coronary angiography consist a complication of the procedure. Clinicians should be aware that intracoronary infusion of contrast medium can lead to physiological changes that lower the ventricular fibrillation threshold.